The impact of menstrual cycle phase on the power profile of female cyclists during a standardised submaximal training ride - Emslie, R.; Viljoen, L.; Beyers, C.; Lamberts, R.; Noordhof, D. (Journal of Science and Cycling, 2024)
Introduction The menstrual cycle is recognized as a multifaceted variable influencing training and performance in female athletes. Over the past two decades, there has been increasing attention on the impact of the menstrual cycle on sports performance. However, scant research has examined its effect on cycling performance. Therefore, this study aims to ascertain whether and how the power profile of female cyclists differs during a 60km submaximal ride conducted in the early follicular phase and mid-luteal phase of the menstrual cycle.